A New Dihydronaphthoquinone from the Flowers of Rosa rugosa and Its Cytotoxicities - Dong, Wei; Wang, Yue-De; Zhou, Kun; Ji, Bing-Kun; Li, Yin-Ke; Zhou, Min; Hu, Qiu-Fen; Gao, Xue-Mei; Ye, Yan-Qing (Asian Journal of Chemistry, 2015)
A new dihydronaphthoquinone, rugosaquinone A (1) was isolated from the flowers of Rosa rugosa. Its structure was elucidated by spectroscopic methods, including extensive 1D NMR and 2D NMR experiments. Compound 1 was tested for its cytotoxicity against five human tumor cell lines, NB4, A549, SHSY5Y, PC3 and MCF7 and it showed potential cytotoxicity against NB4 and SHSY5Y cell lines with IC50 values of 4.2 and 2.8 μM, respectively.